2022
DOI: 10.1111/all.15226
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of lung inflammation on insulin resistance in humans and mice

Abstract: Background:The rates of obesity, its associated diseases, and allergies are raising at alarming rates in most countries. House dust mites (HDM) are highly allergenic and exposure often associates with an urban sedentary indoor lifestyle, also resulting in obesity. The aim of this study was to investigate the epidemiological association and physiological impact of lung inflammation on obesity and glucose homeostasis.Methods: Epidemiological data from 2207 adults of the population-based KORA FF4 cohort were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In ammation can lead to the release of cytokines and other in ammatory molecules that interfere with insulin signaling pathways and promote resistance. 43 Another potential factor contributing to pulmonary IR would be oxidative stress. Increased production of reactive oxygen species can disrupt insulin signaling and impair lung function.…”
Section: Insulin Resistance and Lungmentioning
confidence: 99%
“…In ammation can lead to the release of cytokines and other in ammatory molecules that interfere with insulin signaling pathways and promote resistance. 43 Another potential factor contributing to pulmonary IR would be oxidative stress. Increased production of reactive oxygen species can disrupt insulin signaling and impair lung function.…”
Section: Insulin Resistance and Lungmentioning
confidence: 99%
“…Bronchial smooth muscle cells from asthmatic individuals maintain higher PAR 2 mRNA and protein expression than cells from normal individuals after ex vivo culture (86), suggesting the possibility that epigenetic changes due to the chronic inflammation in the airways may affect PAR 2 expression. We recently showed that insulin regulates PAR 2 expression in primary human airway epithelial cells through the FOXO1 transcription factor (87), which may indicate that insulin resistance, often associated with asthma (88,89), may be associated with alterations of PAR 2 expression. Finally, genetic factors regulating PAR 2 expression cannot be excluded as PAR 2 SNPs have been shown to increase mRNA stability and increase expression of PAR 2 in PBMCs (90) and synovial tissue (91).…”
Section: Regulation Of Par 2 Expressionmentioning
confidence: 99%
“…22 The simultaneous exposure to low-fat (LFD) or high-fat diet (HFD) feeding and HDM extract have been widely used to establish the in vivo models of obesity-related asthma. [23][24][25] In this study, we investigated whether the effects of reticuline on obesity-related asthma in HFD and HDM-induced mouse models are mediated by the JAK/STAT signaling. We believe that this study would provide a theoretical basis for initiating novel promising therapeutic options for obese asthma.…”
Section: Introductionmentioning
confidence: 99%
“…House dust mites (HDM) are highly allergenic and exposure often associates with an urban sedentary indoor lifestyle, also resulting in obesity 22 . The simultaneous exposure to low‐fat (LFD) or high‐fat diet (HFD) feeding and HDM extract have been widely used to establish the in vivo models of obesity‐related asthma 23–25 . In this study, we investigated whether the effects of reticuline on obesity‐related asthma in HFD and HDM‐induced mouse models are mediated by the JAK/STAT signaling.…”
Section: Introductionmentioning
confidence: 99%